WHAT SHOULD A TEACHER KNOW ABOUT MOTIVATION TO LEARN ENGLISH AS A FOREIGN LANGUAGE - Dwi Ima Herminingsih (Publiciana, 2016)
Learning English as a language which is used by the majority people of the world socially, culturally, economically and politically   has many advantages .At the same time, the student whose a language which is different in the linguistics rules and cultural or social norms often face some difficulties to be proficient in learning to using the English. This fact happens because the language is not used in the community where the students conduct their daily activities. Being aware of some obstacles of the students, building the student’s motivation is one of the ways that can eliminate the problems faced by the students. The desire or the interest of the students in acquiring the knowledge of English plays important roles to elevate the student’s achievement. There are two important aspects related with the building of motivation to learn English. The first deals with the motivation to gaining the knowledge of English in the context of social-educational.(classroom-learning context). The second relates to pre-actional, actional and post-actional motivation. The later aspect of motivation asserts that the individual perception of the task, atmosphere, the course content, materials, facilities, personal characteristic of students the roles of the teacher  influence the individual’s classroom learning motivation.